2018
DOI: 10.2147/ijn.s180138
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of gold nanoparticles with <em>Solanum xanthocarpum</em> extract and their in vitro anticancer potential on nasopharyngeal carcinoma cells

Abstract: BackgroundNasopharyngeal cancer (NPC) is one of the subtypes of head and neck cancers. It occurs rarely, and its prevalence depends mainly on geographical location. Modern-day research is focused on coupling nanotechnology and traditional medicine for combating cancers. Gold nanoparticles (AuNPs) were synthesized from Solanum xanthocarpum (Sx) leaf extract using reduction method.MethodsCharacterization of the synthesized AuNPs was done by different techniques such as ultraviolet–visible spectrum absorption, X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 43 publications
0
18
0
2
Order By: Relevance
“…It is possible that the reducing and capping agents are modified at higher temperatures and that the phytochemicals that are involved in the synthesis process at 70 °C differ from the phytochemicals present at 25 °C [ 42 ]. An independent study also reported that the sizes of AuNPs produced from plant extracts were significantly smaller at low temperatures [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the reducing and capping agents are modified at higher temperatures and that the phytochemicals that are involved in the synthesis process at 70 °C differ from the phytochemicals present at 25 °C [ 42 ]. An independent study also reported that the sizes of AuNPs produced from plant extracts were significantly smaller at low temperatures [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“… 159 An interesting study focusing on an essential trace element showed that Na 2 SeO 3 causes cell cycle arrest and affects the mitochondrial-mediated intrinsic caspase pathway with significant anti-proliferative and apoptosis-inducing effects in CNE-2 NPC cells, suggesting that Na 2 SeO 3 might have therapeutic potential in the treatment of NPC. 160 Additionally, human nuclear factor with BRCT domain protein 1 (NFBD1), an amplifier of the p53 pathway and also known as a mediator of DNA damage checkpoint protein (MDC1), is vital for protecting cells from apoptosis in NPC cells mediated through the p53-ROS-mitochondrial pathway. 161 Liver cancer-1 (DLC-1) is lost at high frequency, mainly due to aberrant promoter methylation, and its tumor suppressor roles are not just limited to liver cancer cells as confirmed in multiple cancers.…”
Section: Mitochondria and Ebv-associated Tumorsmentioning
confidence: 99%
“… Silver MCF-7 cells 27.5 μg/mL. [ 132 ] Piper nigrum Silver MCF-7 and Hep-2 cells 52 mL, 54 μg/mL [ 133 ] Ficus religiosa Silver A549 and Hep2 cells 1.9 μg/mL and 1.6 μg/mL [ 134 ] Solanum xanthocarpum Gold HCT 15 human colon cancer [ 135 ] Streptomyces sp. Gold HeLa 350 μg/mL [ 136 ] Evolvulus alsinoides Palladium Human ovarian cancer A2780 cells [ 137 ] Gloriosa superb Platinum and palladium MCF-7 (human breast adenocarcinoma 49.65 ± 1.99% and 36.26 ± 0.91% [ 138 ] Barleria prionitis Platinum Paladium Human breast adenocarcinoma (MCF-7) [ 139 ] Sargassum muticum Iron oxide nanoparticles HeLa cells, MCF-7 cells, HepG2 cells, and human cell lines for leukemia Jurkat 1.1 μg/mL (HepG2), 18.75 ± 2.1 μg/mL (MCF-7), 12.5 ± 1.7 μg/mL (HeLa), and 6.4 ± 2.3 μg/mL (Jurkat) [ 140 ] Albizia lebbeck Zinc oxide MDA-MB 231 and MCF-7 48.5, 48.7, and 60.2 μg/mL [ 107 ] Costus pictus D .…”
Section: Main Textmentioning
confidence: 99%